Negative plate, preparation method of negative plate and lithium ion battery
By designing a second active layer with a large seepage threshold on the negative electrode sheet of the lithium-ion battery, a continuous conductive network is formed, and the problem of lithium-ion surface analysis of the negative electrode during high-ratio charging and discharging is solved, and the safety and electrical performance of the battery are improved.
Patent Information
- Application Number
- CN202411212956.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-30
- Publication Date
- 2025-01-10
AI Technical Summary
During the high-rate charging and discharging process, the safety coating can easily cause lithium-ion surface analysis, resulting in deterioration of the performance of lithium-ion batteries.
The negative electrode sheet design is adopted including a current collector, a first active layer and a second active layer. The seepage threshold of the second active layer is greater than the first active layer. By controlling the conductive agent content, a continuous conductive network is formed to improve electron transmission efficiency and mechanical stability. reduces heat generation from short circuit contact.
It improves the safety performance of lithium-ion batteries, maintains high energy density and good electrical performance, avoids lithium surface analysis, and improves the energy density and electrical performance of lithium ions.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the field of lithium ion batteries, and in particular to a negative electrode sheet, a method for preparing the negative electrode sheet, and a lithium ion battery. Background Art
[0002] In order to improve the safety performance of lithium-ion batteries, current technology is mainly focused on improving the material and structural design of the battery. A common method is to apply a denser safety coating on the surface of the positive electrode current collector or the surface of the negative electrode active coating. This safety coating can increase the resistance between the positive and negative electrodes when an internal short circuit occurs in the battery, thereby slowing down or preventing the generation of short-circuit current, reducing the risk of internal short circuits, and effectively improving the safety performance of the battery. However, the applied safety coating will increase the migration path of lithium ions and increase the overall impedance of the battery. During high-rate charge and discharge, it is easy to cause lithium deposition on the negative electrode surface, deteriorating the performance of the battery. Summary of the invention
[0003] The embodiments of the present invention provide a negative electrode sheet, a method for preparing the negative electrode sheet, and a lithium-ion battery to solve the problem that the safety coating easily causes lithium deposition on the negative electrode surface during high-rate charge and discharge, resulting in deterioration of battery performance.
[0004] Specifically, the present invention provides a negative electrode sheet, including a current collector, a first active layer and a second active layer, wherein the first active layer is arranged on at least one side of the current collector, and the second active layer is arranged on a side of the first active layer away from the current collector; the percolation threshold of the second active layer is greater than the percolation threshold of the first active layer.
[0005] Optionally, a ratio of a percolation threshold of the second active layer to a percolation threshold of the first active layer is 1.2 to 6.0.
[0006] Optionally, a ratio of a percolation threshold of the second active layer to a percolation threshold of the first active layer is 2.0 to 4.5.
[0007] Optionally, the second active layer includes a second conductive agent, and a mass ratio of the second conductive agent in the second active layer satisfies: 0.7B≤C≤1.7B;
[0008] Wherein, B is the percolation threshold of the second active layer, and C is the mass proportion of the second conductive agent in the second active layer.
[0009] Optionally, the thickness of the second active layer is not less than 15 μm.
[0010] Optionally, the second active layer has a thickness of 20 μm to 45 μm.
[0011] Optionally, based on the mass of the first active layer being 100%, the first active layer includes: 93wt% to 98.8wt% of the first active material, 1.2wt% to 5wt% of the first binder, and 0wt% to 2wt% of the first conductive agent;
[0012] And / or, based on the mass of the second active layer being 100%, the second active layer includes: 44wt% to 92wt% of the second active material, 5wt% to 12wt% of the second binder, 0.3wt% to 4wt% of the second conductive agent, and 0wt% to 50wt% of a safety additive.
[0013] Optionally, the first active material includes one or more of graphite, soft carbon, hard carbon, graphite-silicon composite material and lithium titanate;
[0014] The second active material includes one or more of graphite, soft carbon, hard carbon, graphite-silicon composite material and lithium titanate.
[0015] Optionally, the first binder includes one or more of styrene-butadiene rubber, sodium carboxymethyl cellulose, polyacrylonitrile copolymer, sodium polyacrylate, and polyacrylate; the second binder includes one or more of styrene-butadiene rubber, sodium carboxymethyl cellulose, polyacrylonitrile copolymer, sodium polyacrylate, and polyacrylate;
[0016] The first conductive agent includes one or more of conductive carbon black, conductive carbon fiber, carbon nanotube, and graphene; the second conductive agent includes one or more of conductive carbon black, conductive carbon fiber, carbon nanotube, and graphene.
[0017] Optionally, the safety additive includes one or more of barium titanate, strontium titanate, niobium titanate, magnesium oxide and boehmite.
[0018] The present invention also provides a lithium ion battery, which comprises the negative electrode sheet as described in any one of the above items.
[0019] The beneficial effects of the present invention are:
[0020] The present invention can reduce the heat generated by the contact between the positive and negative electrodes during the short circuit in the lithium-ion battery by controlling the percolation threshold of the first active layer and the second active layer, thereby improving the safety performance. In addition, the percolation threshold of the second active layer is relatively large, which means that more conductive agents are required in the second active layer to form a continuous conductive network. More conductive agents are beneficial to improving the electron transmission efficiency or improving the mechanical stability of the electrode. Therefore, during the high-rate charge and discharge process, it is not easy to cause lithium precipitation on the negative electrode surface, and thus the battery performance will not be deteriorated, so that the lithium ions maintain a high energy density and good electrical properties. DETAILED DESCRIPTION
[0021] In order to make the technical problems, technical solutions and beneficial effects solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0022] An embodiment of the present invention provides a negative electrode sheet, including a current collector, a first active layer and a second active layer, wherein the first active layer is formed by coating on a surface of one side of the current collector, and the second active layer is formed by coating on a surface of the first active layer; the percolation threshold of the second active layer is greater than the percolation threshold of the first active layer.
[0023] The percolation threshold in the present invention means that when the content of the conductive agent in the first active layer / the second active layer increases to a certain critical value, the resistivity of the first active layer / the second active layer suddenly drops sharply, and the mass percentage of the conductive agent at this time is the percolation threshold.
[0024] By controlling the percolation threshold of the first active layer and the second active layer, the heat generated by the contact between the positive and negative electrodes during a short circuit in the lithium-ion battery can be reduced, thereby improving safety performance. In addition, the percolation threshold of the second active layer is relatively large, which means that more conductive agents are required in the second active layer to form a continuous conductive network. More conductive agents are beneficial to improving the efficiency of electron transmission or improving the mechanical stability of the electrode. Therefore, during high-rate charge and discharge, it is not easy to induce lithium precipitation on the negative electrode surface, which will not deteriorate the performance of the battery, allowing lithium ions to maintain a high energy density and good electrical properties.
[0025] If the percolation thresholds of the first active layer and the second active layer are increased at the same time, or a single active layer with a larger percolation threshold is set, the entire active layer will require too much conductive agent to form a continuous conductive network, which will reduce the proportion of active materials and have a greater impact on the energy density of the battery.
[0026] In one embodiment of the present invention, the ratio of the percolation threshold of the second active layer to the percolation threshold of the first active layer is 1.2-6.0, that is, 1.2A≤B≤6A; wherein A is the percolation threshold of the first active layer; and B is the percolation threshold of the second active layer.
[0027] Specifically, the ratio of the percolation threshold of the second active layer to the percolation threshold of the first active layer is any one of 1.0, 1.2, 1.5, 2.0, 2.4, 2.5, 3.0, 3.5, 4.0, 4.5, 5.0, 5.5, and 6.0.
[0028] Preferably, the ratio of the percolation threshold of the second active layer to the percolation threshold of the first active layer is 2.0-4.5.
[0029] In one embodiment of the present invention, the second active layer includes a second conductive agent, and the mass ratio of the second conductive agent in the second active layer satisfies: 0.7B≤C≤1.7B; wherein B is the percolation threshold of the second active layer, and C is the mass percentage of the second conductive agent in the second active layer.
[0030] In one embodiment of the present invention, the thickness of the second active layer is not less than 15 μm. Preferably, the thickness of the second active layer is 20 μm to 45 μm. Specifically, the thickness of the second active layer is any one of 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, and 45 μm.
[0031] In one embodiment of the present invention, the thickness of the first active layer is 45 μm to 75 μm.
[0032] In one embodiment of the present invention, based on the mass of the first active layer being 100%, the first active layer comprises: 93wt% to 98.8wt% of the first active material, 1.2wt% to 5wt% of the first binder, and 0wt% to 2wt% of the first conductive agent. Based on the mass of the second active layer being 100%, the second active layer comprises: 45wt% to 92wt% of the second active material, 5wt% to 12wt% of the second binder, 0.3wt% to 4wt% of the second conductive agent, and 0wt% to 50wt% of the safety additive.
[0033] In one embodiment of the present invention, the first negative electrode active material includes one or more of graphite, soft carbon, hard carbon, graphite-silicon composite material and lithium titanate. The second active material includes one or more of graphite, soft carbon, hard carbon, graphite-silicon composite material and lithium titanate. The first binder includes one or more of styrene-butadiene rubber, sodium carboxymethyl cellulose, polyacrylonitrile copolymer, sodium polyacrylate, and polyacrylate; the second binder includes one or more of styrene-butadiene rubber, sodium carboxymethyl cellulose, polyacrylonitrile copolymer, sodium polyacrylate, and polyacrylate. The first conductive agent includes one or more of conductive carbon black, conductive carbon fiber, carbon nanotube, and graphene; the second conductive agent includes one or more of conductive carbon black, conductive carbon fiber, carbon nanotube, and graphene. The safety additive includes one or more of barium titanate, strontium titanate, niobium titanate, magnesium oxide, and boehmite.
[0034] The present invention also provides a method for preparing any one of the above negative electrode sheets, comprising the following steps:
[0035] Artificial graphite, sodium carboxymethyl cellulose and styrene-butadiene rubber are added into deionized water, and a first active layer slurry is prepared through kneading and dispersing processes.
[0036] Artificial graphite, conductive carbon black, sodium carboxymethyl cellulose, styrene-butadiene rubber and magnesium oxide are added into deionized water, and a second active layer slurry is prepared through kneading and dispersing processes.
[0037] The first active layer slurry is coated on the current collector to form a first active layer; the second active layer slurry is coated on the first active layer, and after baking and compaction, the negative electrode sheet is obtained.
[0038] Compared with baking the first active layer and the second active layer separately, coating the first active layer slurry and the second active layer slurry in sequence and then baking can save one baking process and improve production efficiency.
[0039] The present invention also provides a lithium ion battery, wherein the lithium ion battery uses the negative electrode sheet as described in any one of the above items.
[0040] The present invention is further described below by way of examples. However, the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.
[0041] Example 1
[0042] Preparation of negative electrode:
[0043] (1) Preparation of the first active layer slurry: artificial graphite, sodium carboxymethyl cellulose and styrene-butadiene rubber were added into deionized water at a ratio of 96.7:1.6:1.7, and the first active layer slurry was prepared by kneading, dispersing and other processes.
[0044] (2) Preparation of second active layer slurry: Artificial graphite, conductive carbon black, sodium carboxymethyl cellulose, styrene-butadiene rubber and magnesium oxide were added into deionized water at a ratio of 90:0.5:2.5:2.5:4.5, and the second active layer slurry was prepared by kneading, dispersing and other processes.
[0045] (3) The first active layer slurry is coated on a copper foil of 8 μm, and the second active layer slurry is coated on the first active layer. After baking, the thickness of the first active layer is 65 μm, and the thickness of the second active layer is 25 μm. Then, the negative electrode sheet is obtained by a process such as rolling.
[0046] Preparation of positive electrode sheet: Mix the positive electrode active material lithium cobalt oxide, the conductive agent carbon black, and the binder polyvinylidene fluoride, and add the solvent N-methylpyrrolidone to mix and stir to obtain the positive electrode slurry. The above positive electrode slurry is coated on both sides of the positive electrode current collector aluminum foil by an extrusion coater, and then processed by oven baking and roller pressing equipment to obtain the positive electrode sheet.
[0047] The positive electrode sheet, separator and negative electrode sheet prepared above are wound, packaged with aluminum plastic film, and then subjected to conventional lithium battery preparation processes such as baking, liquid injection, hot pressing and forming to obtain a lithium ion battery. Among them, the ratio of the percolation threshold of the second active layer to the percolation threshold of the first active layer is 1.20, and the proportion of the second conductive agent in the second active layer is C=1.16B.
[0048] Example 2
[0049] Preparation of negative electrode:
[0050] (1) Preparation of the first active layer slurry: artificial graphite, sodium carboxymethyl cellulose and styrene-butadiene rubber were added into deionized water at a ratio of 97.4:1.3:1.3, and the first active layer slurry was prepared by kneading, dispersing and other processes.
[0051] (2) Preparation of second active layer slurry: Artificial graphite, conductive carbon black, sodium carboxymethyl cellulose, styrene-butadiene rubber and barium titanate were added into deionized water in a ratio of 85.8:0.8:3:3:7.4, and the second active layer slurry was prepared by kneading, dispersing and other processes.
[0052] (3) The first active layer slurry is coated on a copper foil of 8 μm, and the second active layer slurry is coated on the first active layer. After baking, the thickness of the first active layer is 55 μm, and the thickness of the second active layer is 35 μm. Then, the negative electrode sheet is obtained by rolling and other processes.
[0053] Preparation of positive electrode sheet: Mix the positive electrode active material lithium cobalt oxide, the conductive agent carbon black, and the binder polyvinylidene fluoride, and add the solvent N-methylpyrrolidone to mix and stir to obtain the positive electrode slurry. The above positive electrode slurry is coated on both sides of the positive electrode current collector aluminum foil by an extrusion coater, and then processed by oven baking and roller pressing equipment to obtain the positive electrode sheet.
[0054] The positive electrode sheet, separator and negative electrode sheet prepared above are wound, packaged with aluminum plastic film, and then subjected to conventional lithium battery preparation processes such as baking, liquid injection, hot pressing and forming to obtain a lithium ion battery. Among them, the ratio of the percolation threshold of the second active layer to the percolation threshold of the first active layer is 3.00, and the proportion of the second conductive agent in the second active layer is C=0.92B.
[0055] Example 3
[0056] Preparation of negative electrode:
[0057] (1) Preparation of first active layer slurry: Graphite-silicon composite material, carbon nanotubes, polyacrylonitrile copolymer, sodium carboxymethyl cellulose and styrene-butadiene rubber were added into deionized water at a ratio of 97.4:0.2:1:0.8:0.6, and the first active layer slurry was prepared by kneading, dispersing and other processes.
[0058] (2) Preparation of second active layer slurry: Artificial graphite, conductive carbon black, sodium carboxymethyl cellulose, styrene-butadiene rubber and barium titanate were added into deionized water at a ratio of 75:1.4:3:3:17.6, and the second active layer slurry was prepared by kneading, dispersing and other processes.
[0059] (3) The first active layer slurry is coated on a copper foil of 8 μm, and the second active layer slurry is coated on the first active layer. After baking, the thickness of the first active layer is 55 μm, and the thickness of the second active layer is 35 μm. Then, the negative electrode sheet is obtained by rolling and other processes.
[0060] Preparation of positive electrode sheet: Mix the positive electrode active material lithium cobalt oxide, the conductive agent carbon black, and the binder polyvinylidene fluoride, and add the solvent N-methylpyrrolidone to mix and stir to obtain the positive electrode slurry. The above positive electrode slurry is coated on both sides of the positive electrode current collector aluminum foil by an extrusion coater, and then processed by oven baking and roller pressing equipment to obtain the positive electrode sheet.
[0061] The positive electrode sheet, separator and negative electrode sheet prepared above are wound, packaged with aluminum plastic film, and then subjected to conventional lithium battery preparation processes such as baking, liquid injection, hot pressing and forming to obtain a lithium ion battery. Among them, the ratio of the percolation threshold of the second active layer to the percolation threshold of the first active layer is 5.00, and the proportion of the second conductive agent in the second active layer is C=1.28B.
[0062] Example 4
[0063] Preparation of negative electrode:
[0064] (1) Preparation of first active layer slurry: Graphite-silicon composite material, conductive carbon black, sodium polyacrylate, sodium carboxymethyl cellulose and styrene-butadiene rubber were added into deionized water at a ratio of 97:0.5:1:0.8:0.7, and the first active layer slurry was prepared by kneading, dispersing and other processes.
[0065] (2) Preparation of second active layer slurry: hard carbon, conductive carbon black, sodium polyacrylate, sodium carboxymethyl cellulose and styrene-butadiene rubber were added into deionized water at a ratio of 91:0.3:3:3:2.7, and the second active layer slurry was prepared through kneading, dispersion and other processes.
[0066] (3) The first active layer slurry is coated on a copper foil of 8 μm, and the second active layer slurry is coated on the first active layer. After baking, the thickness of the first active layer is 55 μm, and the thickness of the second active layer is 35 μm. Then, the negative electrode sheet is obtained by rolling and other processes.
[0067] Preparation of positive electrode sheet: Mix the positive electrode active material lithium cobalt oxide, the conductive agent carbon black, and the binder polyvinylidene fluoride, and add the solvent N-methylpyrrolidone to mix and stir to obtain the positive electrode slurry. The above positive electrode slurry is coated on both sides of the positive electrode current collector aluminum foil by an extrusion coater, and then processed by oven baking and roller pressing equipment to obtain the positive electrode sheet.
[0068] The positive electrode sheet, separator and negative electrode sheet prepared above are wound, packaged with aluminum plastic film, and then subjected to conventional lithium battery preparation processes such as baking, liquid injection, hot pressing and forming to obtain a lithium ion battery. Among them, the ratio of the percolation threshold of the second active layer to the percolation threshold of the first active layer is 1.10, and the proportion of the second conductive agent in the second active layer is C=1.00B.
[0069] Example 5
[0070] Preparation of negative electrode:
[0071] (1) Preparation of the first active layer slurry: artificial graphite, sodium carboxymethyl cellulose and styrene-butadiene rubber were added into deionized water at a ratio of 97.4:1.3:1.3, and the first active layer slurry was prepared by kneading, dispersing and other processes.
[0072] (2) Preparation of second active layer slurry: artificial graphite, carbon nanotubes, sodium carboxymethyl cellulose, styrene-butadiene rubber and boehmite were added to deionized water in a ratio of 80.6:0.6:3.5:3.5:11.8, and the second active layer slurry was prepared by kneading, dispersing and other processes.
[0073] (3) The first active layer slurry is coated on a copper foil of 8 μm, and the second active layer slurry is coated on the first active layer. After baking, the thickness of the first active layer is 45 μm, and the thickness of the second active layer is 45 μm. Then, the negative electrode sheet is obtained by a process such as rolling.
[0074] Preparation of positive electrode sheet: Mix the positive electrode active material lithium cobalt oxide, the conductive agent carbon black, and the binder polyvinylidene fluoride, and add the solvent N-methylpyrrolidone to mix and stir to obtain the positive electrode slurry. The above positive electrode slurry is coated on both sides of the positive electrode current collector aluminum foil by an extrusion coater, and then processed by oven baking and roller pressing equipment to obtain the positive electrode sheet.
[0075] The positive electrode sheet, separator and negative electrode sheet prepared above are wound, packaged with aluminum plastic film, and then subjected to conventional lithium battery preparation processes such as baking, liquid injection, hot pressing and forming to obtain a lithium ion battery. Among them, the ratio of the percolation threshold of the second active layer to the percolation threshold of the first active layer is 6.00, and the proportion of the second conductive agent in the second active layer is C=1.60B.
[0076] Example 6
[0077] Preparation of negative electrode:
[0078] (1) Preparation of the first active layer slurry: soft carbon, sodium carboxymethyl cellulose and styrene-butadiene rubber were added into deionized water at a ratio of 97.4:1.3:1.3, and the first active layer slurry was prepared by kneading, dispersing and other processes.
[0079] (2) Preparation of second active layer slurry: Artificial graphite, conductive carbon black, sodium carboxymethyl cellulose, styrene-butadiene rubber and magnesium oxide were added into deionized water at a ratio of 73:2.1:2.5:2.5:19.9, and the second active layer slurry was prepared by kneading, dispersing and other processes.
[0080] (3) The first active layer slurry is coated on a copper foil of 8 μm, and the second active layer slurry is coated on the first active layer. After baking, the thickness of the first active layer is 55 μm, and the thickness of the second active layer is 35 μm. Then, the negative electrode sheet is obtained by rolling and other processes.
[0081] Preparation of positive electrode sheet: Mix the positive electrode active material lithium cobalt oxide, the conductive agent carbon black, and the binder polyvinylidene fluoride, and add the solvent N-methylpyrrolidone to mix and stir to obtain the positive electrode slurry. The above positive electrode slurry is coated on both sides of the positive electrode current collector aluminum foil by an extrusion coater, and then processed by oven baking and roller pressing equipment to obtain the positive electrode sheet.
[0082] The positive electrode sheet, separator and negative electrode sheet prepared above are wound, packaged with aluminum plastic film, and then subjected to conventional lithium battery preparation processes such as baking, liquid injection, hot pressing and forming to obtain a lithium ion battery. Among them, the ratio of the percolation threshold of the second active layer to the percolation threshold of the first active layer is 6.50, and the proportion of the second conductive agent in the second active layer is C=1.42B.
[0083] Example 7
[0084] Preparation of negative electrode:
[0085] (1) Preparation of first active layer slurry: artificial graphite, conductive carbon black, sodium carboxymethyl cellulose and styrene-butadiene rubber were added into deionized water at a ratio of 96.4:0.6:1.5:1.5, and the first active layer slurry was prepared by kneading, dispersing and other processes.
[0086] (2) Preparation of second active layer slurry: Artificial graphite, conductive carbon black, sodium carboxymethyl cellulose, styrene-butadiene rubber and magnesium oxide were added into deionized water at a ratio of 62:0.7:3:3:31.3, and the second active layer slurry was prepared by kneading, dispersing and other processes.
[0087] (3) The first active layer slurry is coated on a copper foil of 8 μm, and the second active layer slurry is coated on the first active layer. After baking, the thickness of the first active layer is 65 μm, and the thickness of the second active layer is 25 μm. Then, the negative electrode sheet is obtained by a process such as rolling.
[0088] Preparation of positive electrode sheet: Mix the positive electrode active material lithium cobalt oxide, the conductive agent carbon black, and the binder polyvinylidene fluoride, and add the solvent N-methylpyrrolidone to mix and stir to obtain the positive electrode slurry. The above positive electrode slurry is coated on both sides of the positive electrode current collector aluminum foil by an extrusion coater, and then processed by oven baking and roller pressing equipment to obtain the positive electrode sheet.
[0089] The positive electrode sheet, separator and negative electrode sheet prepared above are wound, packaged with aluminum plastic film, and then subjected to conventional lithium battery preparation processes such as baking, liquid injection, hot pressing and forming to obtain a lithium ion battery. Among them, the ratio of the percolation threshold of the second active layer to the percolation threshold of the first active layer is 4.50, and the proportion of the second conductive agent in the second active layer is C=0.43B.
[0090] Example 8
[0091] Preparation of negative electrode:
[0092] (1) Preparation of the first active layer slurry: artificial graphite, sodium carboxymethyl cellulose and styrene-butadiene rubber were added into deionized water at a ratio of 97:1.5:1.5, and the first active layer slurry was prepared by kneading, dispersing and other processes.
[0093] (2) Preparation of second active layer slurry: Artificial graphite, conductive carbon black, sodium carboxymethyl cellulose, styrene-butadiene rubber and niobium titanate were added into deionized water in a ratio of 84:2.3:3:3:7.7, and the second active layer slurry was prepared by kneading, dispersing and other processes.
[0094] (3) The first active layer slurry is coated on a copper foil of 8 μm, and the second active layer slurry is coated on the first active layer. After baking, the thickness of the first active layer is 55 μm, and the thickness of the second active layer is 35 μm. Then, the negative electrode sheet is obtained by rolling and other processes.
[0095] Preparation of positive electrode sheet: Mix the positive electrode active material lithium cobalt oxide, the conductive agent carbon black, and the binder polyvinylidene fluoride, and add the solvent N-methylpyrrolidone to mix and stir to obtain the positive electrode slurry. The above positive electrode slurry is coated on both sides of the positive electrode current collector aluminum foil by an extrusion coater, and then processed by oven baking and roller pressing equipment to obtain the positive electrode sheet.
[0096] The positive electrode sheet, separator and negative electrode sheet prepared above are wound, packaged with aluminum plastic film, and then subjected to conventional lithium battery preparation processes such as baking, liquid injection, hot pressing and forming to obtain a lithium ion battery. Among them, the ratio of the percolation threshold of the second active layer to the percolation threshold of the first active layer is 3.50, and the proportion of the second conductive agent in the second active layer is C=2.00B.
[0097] Embodiment 9:
[0098] Preparation of negative electrode:
[0099] (1) Preparation of the first active layer slurry: artificial graphite, sodium carboxymethyl cellulose and styrene-butadiene rubber were added into deionized water at a ratio of 97.4:1.3:1.3, and the first active layer slurry was prepared by kneading, dispersing and other processes.
[0100] (2) Preparation of second active layer slurry: artificial graphite, carbon nanotubes, sodium carboxymethyl cellulose, styrene-butadiene rubber and boehmite were added into deionized water at a ratio of 76:0.3:2:2:19.7, and the second active layer slurry was prepared by kneading, dispersing and other processes.
[0101] (3) The first active layer slurry is coated on a copper foil of 8 μm, and the second active layer slurry is coated on the first active layer. After baking, the thickness of the first active layer is 75 μm, and the thickness of the second active layer is 15 μm. Then, the negative electrode sheet is obtained by rolling and other processes.
[0102] Preparation of positive electrode sheet: Mix the positive electrode active material lithium cobalt oxide, the conductive agent carbon black, and the binder polyvinylidene fluoride, and add the solvent N-methylpyrrolidone to mix and stir to obtain the positive electrode slurry. The above positive electrode slurry is coated on both sides of the positive electrode current collector aluminum foil by an extrusion coater, and then processed by oven baking and roller pressing equipment to obtain the positive electrode sheet.
[0103] The positive electrode sheet, separator and negative electrode sheet prepared above are wound, packaged with aluminum plastic film, and then subjected to conventional lithium battery preparation processes such as baking, liquid injection, hot pressing and forming to obtain a lithium ion battery. Among them, the ratio of the percolation threshold of the second active layer to the percolation threshold of the first active layer is 2.00, and the proportion of the second conductive agent in the second active layer is C=1.10B.
[0104] Embodiment 10:
[0105] Preparation of negative electrode:
[0106] (1) Preparation of the first active layer slurry: Graphite-silicon composite material, conductive carbon black, sodium carboxymethyl cellulose and styrene-butadiene rubber were added to deionized water in a ratio of 97:0.5:1.2:1.3, and the first active layer slurry was prepared by kneading, dispersing and other processes.
[0107] (2) Preparation of second active layer slurry: Artificial graphite, conductive carbon black, sodium carboxymethyl cellulose, styrene-butadiene rubber and magnesium oxide were added into deionized water in a ratio of 61:1.2:1.5:2:34.3, and the second active layer slurry was prepared by kneading, dispersing and other processes.
[0108] (3) The first active layer slurry is coated on a copper foil of 8 μm, and the second active layer slurry is coated on the first active layer. After baking, the thickness of the first active layer is 65 μm, and the thickness of the second active layer is 25 μm. Then, the negative electrode sheet is obtained by a process such as rolling.
[0109] Preparation of positive electrode sheet: Mix the positive electrode active material lithium cobalt oxide, the conductive agent carbon black, and the binder polyvinylidene fluoride, and add the solvent N-methylpyrrolidone to mix and stir to obtain the positive electrode slurry. The above positive electrode slurry is coated on both sides of the positive electrode current collector aluminum foil by an extrusion coater, and then processed by oven baking and roller pressing equipment to obtain the positive electrode sheet.
[0110] The positive electrode sheet, separator and negative electrode sheet prepared above are wound, packaged with aluminum plastic film, and then subjected to conventional lithium battery preparation processes such as baking, liquid injection, hot pressing and forming to obtain a lithium ion battery. Among them, the ratio of the percolation threshold of the second active layer to the percolation threshold of the first active layer is 4.00, and the proportion of the second conductive agent in the second active layer is C=0.70B.
[0111] Embodiment 11:
[0112] Preparation of negative electrode:
[0113] (1) Preparation of the first active layer slurry: artificial graphite, sodium carboxymethyl cellulose and styrene-butadiene rubber were added into deionized water at a ratio of 97.4:1.3:1.3, and the first active layer slurry was prepared by kneading, dispersing and other processes.
[0114] (2) Preparation of second active layer slurry: Artificial graphite, conductive carbon black, sodium carboxymethyl cellulose, styrene-butadiene rubber and barium titanate were added into deionized water at a ratio of 74:0.6:3:3:19.4, and the second active layer slurry was prepared by kneading, dispersing and other processes.
[0115] (3) The first active layer slurry is coated on a copper foil of 8 μm, and the second active layer slurry is coated on the first active layer. After baking, the thickness of the first active layer is 70 μm, and the thickness of the second active layer is 20 μm. Then, the negative electrode sheet is obtained by rolling and other processes.
[0116] Preparation of positive electrode sheet: Mix the positive electrode active material lithium cobalt oxide, the conductive agent carbon black, and the binder polyvinylidene fluoride, and add the solvent N-methylpyrrolidone to mix and stir to obtain the positive electrode slurry. The above positive electrode slurry is coated on both sides of the positive electrode current collector aluminum foil by an extrusion coater, and then processed by oven baking and roller pressing equipment to obtain the positive electrode sheet.
[0117] The positive electrode sheet, separator and negative electrode sheet prepared above are wound, packaged with aluminum plastic film, and then subjected to conventional lithium battery preparation processes such as baking, liquid injection, hot pressing and forming to obtain a lithium ion battery. Among them, the ratio of the percolation threshold of the second active layer to the percolation threshold of the first active layer is 3.00, and the proportion of the second conductive agent in the second active layer is C=0.92B.
[0118] Embodiment 12:
[0119] Preparation of negative electrode:
[0120] (1) Preparation of the first active layer slurry: artificial graphite, sodium carboxymethyl cellulose and styrene-butadiene rubber were added into deionized water at a ratio of 97.4:1.3:1.3, and the first active layer slurry was prepared by kneading, dispersing and other processes.
[0121] (2) Preparation of second active layer slurry: Artificial graphite, conductive carbon black, sodium carboxymethyl cellulose, styrene-butadiene rubber and barium titanate were added into deionized water at a ratio of 92.5:0.3:3:3:1.2, and the second active layer slurry was prepared by kneading, dispersing and other processes.
[0122] (3) The first active layer slurry is coated on a copper foil of 8 μm, and the second active layer slurry is coated on the first active layer. After baking, the thickness of the first active layer is 45 μm, and the thickness of the second active layer is 45 μm. Then, the negative electrode sheet is obtained by a process such as rolling.
[0123] Preparation of positive electrode sheet: Mix the positive electrode active material lithium cobalt oxide, the conductive agent carbon black, and the binder polyvinylidene fluoride, and add the solvent N-methylpyrrolidone to mix and stir to obtain the positive electrode slurry. The above positive electrode slurry is coated on both sides of the positive electrode current collector aluminum foil by an extrusion coater, and then processed by oven baking and roller pressing equipment to obtain the positive electrode sheet.
[0124] The positive electrode sheet, separator and negative electrode sheet prepared above are wound, packaged with aluminum plastic film, and then subjected to conventional lithium battery preparation processes such as baking, liquid injection, hot pressing and forming to obtain a lithium ion battery. Among them, the ratio of the percolation threshold of the second active layer to the percolation threshold of the first active layer is 3.00, and the proportion of the second conductive agent in the second active layer is C=0.92B.
[0125] Embodiment 13:
[0126] Preparation of negative electrode:
[0127] (1) Preparation of the first active layer slurry: artificial graphite, sodium carboxymethyl cellulose and styrene-butadiene rubber were added into deionized water at a ratio of 97.4:1.3:1.3, and the first active layer slurry was prepared by kneading, dispersing and other processes.
[0128] (2) Preparation of second active layer slurry: Artificial graphite, conductive carbon black, sodium carboxymethyl cellulose, styrene-butadiene rubber and barium titanate were added into deionized water at a ratio of 61.4:1.0:3:3:31.6, and the second active layer slurry was prepared by kneading, dispersing and other processes.
[0129] (3) The first active layer slurry is coated on a copper foil of 8 μm, and the second active layer slurry is coated on the first active layer. After baking, the thickness of the first active layer is 75 μm, and the thickness of the second active layer is 15 μm. Then, the negative electrode sheet is obtained by rolling and other processes.
[0130] Preparation of positive electrode sheet: Mix the positive electrode active material lithium cobalt oxide, the conductive agent carbon black, and the binder polyvinylidene fluoride, and add the solvent N-methylpyrrolidone to mix and stir to obtain the positive electrode slurry. The above positive electrode slurry is coated on both sides of the positive electrode current collector aluminum foil by an extrusion coater, and then processed by oven baking and roller pressing equipment to obtain the positive electrode sheet.
[0131] The positive electrode sheet, separator and negative electrode sheet prepared above are wound, packaged with aluminum plastic film, and then subjected to conventional lithium battery preparation processes such as baking, liquid injection, hot pressing and forming to obtain a lithium ion battery. Among them, the ratio of the percolation threshold of the second active layer to the percolation threshold of the first active layer is 3.00, and the proportion of the second conductive agent in the second active layer is C=0.92B.
[0132] Comparative Example 1:
[0133] Artificial graphite, conductive carbon black, sodium carboxymethyl cellulose and styrene-butadiene rubber were added to deionized water in a ratio of 97:0.5:1.2:1.3, and slurry was prepared through kneading, dispersion and other processes. The slurry was then coated on 8μm copper foil, and after baking, the thickness of the active layer was 90μm. The electrode was then rolled and other processes were used to obtain the negative electrode.
[0134] The positive electrode active material lithium cobalt oxide, the conductive agent carbon black, and the binder polyvinylidene fluoride are mixed, and the solvent N-methylpyrrolidone is added for mixing and stirring to obtain the positive electrode slurry. The positive electrode slurry is coated on both sides of the positive electrode current collector aluminum foil by an extrusion coater, and then processed by an oven baking and roller pressing equipment to obtain a positive electrode sheet.
[0135] The positive electrode sheet, separator and negative electrode sheet prepared above are wound, packaged with aluminum-plastic film, and then subjected to conventional lithium battery preparation processes such as baking, liquid injection, hot pressing and formation to obtain a lithium-ion battery.
[0136] Comparative Example 2
[0137] Preparation of negative electrode:
[0138] (1) Preparation of first active layer slurry: Graphite-silicon composite material, conductive carbon fiber, polyacrylate, sodium carboxymethyl cellulose and styrene-butadiene rubber were added into deionized water at a ratio of 96.7:0.3:1:1:1, and the first active layer slurry was prepared by kneading, dispersing and other processes.
[0139] (2) Preparation of second active layer slurry: artificial graphite, conductive carbon black, sodium carboxymethyl cellulose and styrene-butadiene rubber were added into deionized water in a ratio of 92:0.5:3.5:4, and the second active layer slurry was prepared by kneading, dispersing and other processes.
[0140] (3) The first active layer slurry is coated on a copper foil of 8 μm, and the second active layer slurry is coated on the first active layer. After baking, the thickness of the first active layer is 65 μm, and the thickness of the second active layer is 25 μm. Then, the negative electrode sheet is obtained by a process such as rolling.
[0141] Preparation of positive electrode sheet: Mix the positive electrode active material lithium cobalt oxide, the conductive agent carbon black, and the binder polyvinylidene fluoride, and add the solvent N-methylpyrrolidone to mix and stir to obtain the positive electrode slurry. The above positive electrode slurry is coated on both sides of the positive electrode current collector aluminum foil by an extrusion coater, and then processed by oven baking and roller pressing equipment to obtain the positive electrode sheet.
[0142] The positive electrode sheet, separator and negative electrode sheet prepared above are wound, packaged with aluminum plastic film, and then subjected to conventional lithium battery preparation processes such as baking, liquid injection, hot pressing and forming to obtain a lithium ion battery. Among them, the ratio of the percolation threshold of the second active layer to the percolation threshold of the first active layer is 0.90, and the proportion of the second conductive agent in the second active layer is C=1.25B.
[0143] Performance Testing
[0144] The lithium ion batteries obtained in Examples 1-13 and Comparative Examples 1-2 were tested as follows:
[0145] Percolation threshold test: Use a resistivity tester (BER1300 from Yuanneng Technology) to test the resistivity values of the first active layer and the second active layer with different contents of conductive agents in Examples 1-13 and Comparative Example 2. After calibrating the thickness and resistance values measured by the equipment, place the sample on the test bench, and record the sample resistivity value after the test is completed. Perform 15 parallel tests on the same sample, record the values, and calculate the average. When the content of the conductive agent increases to a certain critical value, its resistivity suddenly drops sharply. The mass percentage content of the conductive agent at this time is the percolation threshold. In order to make the results have comparative significance, the same conductive agent is used for the first active layer and the second active layer during the percolation threshold test.
[0146] Center puncture test: The lithium-ion batteries obtained in Examples 1-13 and Comparative Examples 1-2 were subjected to center puncture tests respectively. The lithium-ion battery was charged to 4.35V at a constant current of 0.7C at room temperature, and then charged to a cut-off current of 0.05C at a constant voltage. The lithium-ion battery was then transferred to a puncture test device, and at a room temperature of 25°C, a steel nail with a diameter of 3mm was used to uniformly penetrate the center of the lithium-ion battery at a speed of 20mm / min, and retained for 5 minutes. The battery passed the test if it did not catch fire or explode. 20 batteries were tested for each example and comparative example, and the pass rate of the center puncture test was used as an indicator for evaluating safety.
[0147] Normal temperature cycle test: The lithium ion batteries obtained in Examples 1-13 and Comparative Examples 1-2 were charged to 50% SOC at a room temperature of 25°C at 1C constant current, then charged to 4.35V at 0.65C constant current, with a cut-off current of 0.05C; 2. discharged to 3.0V at 0.5C constant current; steps ① and ② were cycled for 800T, and the capacity retention rate after the cycle was recorded. Three batteries were tested for each example and comparative example. The results are recorded in Table 1.
[0148] Table 1 Performance test data
[0149]
[0150] Through the above table, we can draw the following conclusions by comparison:
[0151] According to Example 1, Example 9, Example 2, Example 10, Example 7, Example 5, and Example 6, as the percolation threshold of the second active layer increases, the pass rate of the center puncture test of the lithium-ion battery gradually increases, and the energy density loss is low. However, the percolation threshold of the second active layer is too high (B>6A), resulting in an excessively high content of the second conductive agent in the second active layer, and a relatively decreased content of the second active material, which deteriorates the cycle performance of the lithium-ion battery and no longer meets 800T-80%.
[0152] According to Comparative Example 2 and Example 4, if the percolation threshold of the second active layer is too low (B<1.2A) and the content of the second conductive agent in the second active layer is low, the heat of the lithium-ion battery at the puncture point cannot be timely and effectively conducted and dissipated during the puncture test, resulting in a sharp rise in the local temperature and promoting the expansion of the thermal runaway reaction, thus making it difficult for the lithium-ion battery to pass the center puncture test.
[0153] According to Example 2, Example 8, Example 7, and Example 3, when the ratio of the percolation threshold of the second active layer to the percolation threshold of the first active layer in different groups of lithium-ion batteries is close, increasing the content of the second conductive agent in the second active layer to exceed the percolation threshold of the second active layer will lead to a decrease in the pass rate of the center needle penetration test of the lithium-ion battery. The reason is that if the content of the second conductive agent is too high, the current density inside the lithium-ion battery will be too large, and the heat will be concentrated and difficult to dissipate, thereby increasing the possibility of thermal runaway, thereby reducing the pass rate of the center needle penetration test of the lithium-ion battery.
[0154] According to Example 2 and Examples 11 to 13, when the ratio of the percolation threshold of the second active layer in the lithium-ion battery is the same as the percolation threshold of the first active layer, and the proportion of the second conductive agent in the second active layer is the same, as the thickness of the second active layer increases, the proportion of the second active layer thickness in the entire active layer increases, that is, the proportion of the second conductive agent in the entire active layer increases, resulting in excessive current density inside the lithium-ion battery, concentrated heat that is difficult to dissipate, thereby increasing the possibility of thermal runaway, and thus reducing the pass rate of the center puncture test of the lithium-ion battery.
[0155] The embodiments described above are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. Such modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention, and should all be included in the protection scope of the present invention.
Claims
1. A negative electrode sheet, characterized in that: The invention comprises a current collector, a first active layer and a second active layer, wherein the first active layer is arranged on at least one side of the current collector, and the second active layer is arranged on a side of the first active layer away from the current collector; and the percolation threshold of the second active layer is greater than the percolation threshold of the first active layer.
2. The negative electrode sheet according to claim 1, characterized in that: A ratio of a percolation threshold of the second active layer to a percolation threshold of the first active layer is 1.2 to 6.
0.
3. The negative electrode sheet according to claim 2, characterized in that: A ratio of a percolation threshold of the second active layer to a percolation threshold of the first active layer is 2.0 to 4.
5.
4. The negative electrode sheet according to claim 1, characterized in that: The second active layer includes a second conductive agent, and the mass ratio of the second conductive agent in the second active layer satisfies: 0.7B≤C≤1.7B; Wherein, B is the percolation threshold of the second active layer, and C is the mass proportion of the second conductive agent in the second active layer.
5. The negative electrode sheet according to claim 1, characterized in that: The thickness of the second active layer is not less than 15 μm.
6. The negative electrode sheet according to claim 5, characterized in that: The second active layer has a thickness of 20 μm to 45 μm.
7. The negative electrode sheet according to claim 1, characterized in that: Taking the mass of the first active layer as 100%, the first active layer includes: 93wt% to 98.8wt% of the first active material, 1.2wt% to 5wt% of the first binder, and 0wt% to 2wt% of the first conductive agent; And / or, based on the mass of the second active layer being 100%, the second active layer includes: 44wt% to 92wt% of the second active material, 5wt% to 12wt% of the second binder, 0.3wt% to 4wt% of the second conductive agent, and 0wt% to 50wt% of a safety additive.
8. The negative electrode sheet according to claim 7, characterized in that: The first active material includes one or more of graphite, soft carbon, hard carbon, graphite-silicon composite material and lithium titanate; The second active material includes one or more of graphite, soft carbon, hard carbon, graphite-silicon composite material and lithium titanate.
9. The negative electrode sheet according to claim 7, characterized in that: The first binder includes one or more of styrene-butadiene rubber, sodium carboxymethyl cellulose, polyacrylonitrile copolymer, sodium polyacrylate, and polyacrylate; the second binder includes one or more of styrene-butadiene rubber, sodium carboxymethyl cellulose, polyacrylonitrile copolymer, sodium polyacrylate, and polyacrylate; The first conductive agent includes one or more of conductive carbon black, conductive carbon fiber, carbon nanotube, and graphene; the second conductive agent includes one or more of conductive carbon black, conductive carbon fiber, carbon nanotube, and graphene; The safety additive includes one or more of barium titanate, strontium titanate, niobium titanate, magnesium oxide and boehmite.
10. A method for preparing a negative electrode sheet according to any one of claims 1 to 9, characterized in that: The steps include: Adding artificial graphite, sodium carboxymethyl cellulose and styrene-butadiene rubber into deionized water, and preparing a first active layer slurry through kneading and dispersing processes; Adding artificial graphite, conductive carbon black, sodium carboxymethyl cellulose, styrene-butadiene rubber and magnesium oxide into deionized water, and preparing a second active layer slurry through kneading and dispersing processes; Applying the first active layer slurry on the current collector to form a first active layer; The second active layer slurry is coated on the first active layer, and after baking and compacting, the negative electrode sheet is obtained.
11. A lithium ion battery, characterized in that: A negative electrode sheet comprising any one of claims 1 to 9.